2014
DOI: 10.1021/nn501495a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle as Signaling Protein Mimic: Robust Structural and Functional Modulation of CaMKII upon Specific Binding to Fullerene C60 Nanocrystals

Abstract: In a biological environment, nanoparticles encounter and interact with thousands of proteins, forming a protein corona on the surface of the nanoparticles, but these interactions are oftentimes perceived as nonspecific protein adsorption, with protein unfolding and deactivation as the most likely consequences. The potential of a nanoparticle-protein interaction to mimic a protein-protein interaction in a cellular signaling process, characterized by stringent binding specificity and robust functional modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 51 publications
1
31
0
1
Order By: Relevance
“…In a key study, C 60 fullerenes were shown to act as specific signaling "mimics" (26). Hence, fullerenes were shown to interact with and modulate the function of the Ca 2+ /calmodulin-dependent protein kinase II (CaMKII), a multimeric intracellular serine/threonine kinase central to Ca 2+ signal transduction, in a manner similar to the welldocumented interaction between the NMDA (N-methyl-D-aspartate) receptor subunit NR2B protein and CaMKII (26).…”
Section: Towards a Molecular Nanotoxicologymentioning
confidence: 99%
See 1 more Smart Citation
“…In a key study, C 60 fullerenes were shown to act as specific signaling "mimics" (26). Hence, fullerenes were shown to interact with and modulate the function of the Ca 2+ /calmodulin-dependent protein kinase II (CaMKII), a multimeric intracellular serine/threonine kinase central to Ca 2+ signal transduction, in a manner similar to the welldocumented interaction between the NMDA (N-methyl-D-aspartate) receptor subunit NR2B protein and CaMKII (26).…”
Section: Towards a Molecular Nanotoxicologymentioning
confidence: 99%
“…Hence, fullerenes were shown to interact with and modulate the function of the Ca 2+ /calmodulin-dependent protein kinase II (CaMKII), a multimeric intracellular serine/threonine kinase central to Ca 2+ signal transduction, in a manner similar to the welldocumented interaction between the NMDA (N-methyl-D-aspartate) receptor subunit NR2B protein and CaMKII (26). The results from this detailed experimental study thus suggested that an inorganic nanoparticle can act like a cellular signaling protein and underscored the importance of specific interactions between nanoparticles and proteins.…”
Section: Towards a Molecular Nanotoxicologymentioning
confidence: 99%
“…НаноC60 модулиру-ет Ca 2+ /кальмодулинзависимую протеинкиназу II (CaMKII), мультимерную внутриклеточную серин/ треонинспецифичную протеинкиназу, необходимую для трансдукции сигнала Ca 2+ , конкурируя со взаи-модействием субъединицы рецептора NMDA NR2B и CaMKII [48]. Способность наноC60 поддерживать киназную активность CaMKII может в перспективе оказаться полезной для терапевтического исполь-зования фуллерена C 60 .…”
Section: фуллерен и биологические молекулыunclassified
“…For example, nano-C 60 can interact with and modulate the function of Ca 2+ /calmodulin-dependent protein kinase II (CaMKII), a multimeric intracellular serine/threonine-specific kinase central to Ca 2+ signal transduction, by a mechanism that competes with the well-documented interaction between the NMDA receptor subunit NR2B and CaMKII. 287 The example of specific interaction between nanoparticles and cellular signalling proteins may have significant implications for the potential therapeutic applications of fullerene C 60 .…”
Section: Iii3 Biomedical Applicationsmentioning
confidence: 99%